PRANGOS PLATYCHLAENA BOISS ESSENTIAL OILS: A NOVEL STUDY ON ITS TOXICITY, ANTIBACTERIAL ACTIVITY AND CHEMICAL COMPOSITIONS EFFECT ON BURN RATS - & et al., Rahman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The Prangos platychlaena Boiss belonged to the family of Apiaceae is a native medicinal plant of Kurdistan-Iraq. The stem, leaves and flowers of the plant were collected in the mountain of Halgurd of the Kurdistan region of Iraq, and hydrodistilated to obtain the volatile compounds, using both Gas Chromatography ( GC ) and Gas chromatography/ Mass spectroscopy (GC/MS). The results showed that the P. platychlaena Boiss essential oils containing several compounds such as Sylvestrene, α-Pinene oxide, (Z)-Epoxy-ocimene, Borneol, epi-Longipinanol, Germacrene D-4-ol, epi-α-Cadinol, 3-Thujanol acetate and Acorenone with different amount which were not found in any other Prangos species, and all showed antibacterial activity. This experiment was concducted to reveal the toxicity of flowers essentail oils of the P.platychlaena Boiss on skin burns of the rat. The results revealed that the base cream which contains 1% of the essentail oils showd less time in healing wounds in comparing with the other groups. Histological examination of the treated ones showed significantly the formation of new epiderm in those rats which were receiving the base cream containg 1% essentail oils. These finding sugested that the essentail oils of this plant can be used as a surface treatment agent for the human burns.